Honey Bee Parasitic Mite Contains the Sensilla-Rich Sensory Organ on the Foreleg Tarsus Expressing Ionotropic Receptors With Conserved Functions - Lei, Jing; Liu, Qiushi; Kadowaki, Tatsuhiko (Frontiers in Physiology, 2019)
Honey bee parasitic mites (Tropilaelaps mercedesae and Varroa destructor) detect temperature, humidity, and odor but the underlying sensory mechanisms are poorly understood. To uncover how T. mercedesae responds to environmental stimuli inside a hive, we first identified the sensilla-rich sensory organ on the foreleg tarsus. The organ appeared to correspond to Haller’s organ in ticks and contained four types of sensilla, which may respond to different stimuli based on their morphology. We searched for differentially expressed genes between the forelegs and hindlegs to identify mRNAs potentially associated with the sensory organ. The forelegs were enriched with mRNAs encoding sensory proteins such as ionotropic receptors (IRs) and gustatory receptors, as well as proteins involved in ciliary transport. We also found that T. mercedesae IR25a and IR93a were capable of rescuing temperature and humidity preference defects in Drosophila melanogaster IR25a and IR93a mutants. These results demonstrate that the structures and physiological functions of ancient IRs have been conserved during arthropod evolution. Our study provides insight into the sensory mechanisms of honey bee parasitic mites, as well as potential targets for methods to control the most serious honey bee pest.